Análise da prevalência de fatores de risco cardiometabólico em mulheres no climatério - Oliveira, Aline Keli de (2021)
Introduction: During menopause, several factors lead to an increased incidence and prevalence of cardiometabolic diseases in women compared to men of the same age and women before menopause. Objective: To analyze the prevalence of metabolic syndrome in climacteric women and to correlate those attending basic family health units in Uberlândia-MG. Methods: This is a cross-sectional and descriptive study with data referring to 1240 (one thousand two hundred and forty) climacteric women, attended by Basic Family Health Units (UBSF) in the city of Uberlândia-MG. According to data from medical records and laboratory tests, cardiovascular risk factors were evaluated, namely: hypertension, diabetes, dyslipidemia and obesity. Descriptive data analysis was performed, and the frequency of these factors was analyzed with clinical and anthropometric assessment using chi-square. The 5% significance level. Results: Cardiometabolic factors: dyslipidemia had a prevalence of 29.4% in the sample surveyed, SAH in 59.1% of patients, diabetes in 7.2% and obesity in 28%. Of the patients who participated in the study, 27% had no risk factors and 31.3% a risk factor, 24.1% had two risk factors and 17% three or more risk factors for developing metabolic syndrome. Neither the period before or after menopause, nor the use of hormone therapy for menopause were factors influencing the number of risk factors for the development of cardiometabolic diseases. The age group seems to be the most influencing factor. Conclusion: The prevalence of risk factors for metabolic syndrome in climacteric women attending UBSFs is relatively high, and the data obtained suggest that age is one of the most important causes of the increase in the number of these factors, unrelated to the period of menopause and/or the use of hormone therapy for menopause.